High performance nanostructured bismuth oxide-cobaltite as a durable oxygen electrode for reversible solid oxide cells - Ai, N.; Chen, M.; He, S.; Chen, K.; Zhang, T.; Jiang, San Ping (R S C Publications, 2018)
The high reactivity between bismuth oxide and cobaltite oxygen electrodes is a bottleneck in developing active and reliable bismuth oxide–cobaltite composite oxygen electrodes for solid oxide cells (SOCs). Herein, a Sr-free Sm0.95Co0.95Pd0.05O3−δ (SmCPd) oxygen electrode decorated with nanoscale Er0.4Bi1.6O3 (ESB) is synthesized and assembled on a barrier-layer-free Y2O3–ZrO2 (YSZ) electrolyte film. The cell with the ESB decorated SmCPd composite oxygen electrode exhibits a peak power density of 1.81 W cm−2 at 750 °C and 0.58 W cm−2 at 650 °C. More importantly, excellent operating stability is achieved in the fuel cell mode at 600 °C for 500 h, and in electrolysis and reversible modes at 750 °C for over 200 h. The results demonstrate the feasibility of applying bismuth oxide–cobaltite composite oxygen electrodes in developing high-performance and durable SOCs.